Zagadnienia onomastyczne w dorobku zielonogórskich językoznawców = Onomastic issues in the achievements of linguists from Zielona Góra - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the considerations undertaken in this article is to define the scope of onomastics research conducted by linguists from Zielona Góra. The research material of the study consists of works by Polish language teachers associated with the university in Zielona Góra, either permanently or for a specific period of time. In the latter case, only the achievements of researchers that arose during their employment in Zielona Góra were taken into account. The analysis showed that onomastics was and still is one of the important research areas of the Zielona Góra linguists, with toponymy and chrematonimia among the subdisciplines most popular.
Keywords: onomastyka; toponimia; chrematonimia; antroponimia; onomastyka literacka; poprawność nazw własnych; badania zielonogórskich językoznawców; onomastics; toponymy; anthroponymy; literary onomastics; correctness of proper names; research of linguists from Zielona Góra